PolyQ 2.0: an improved version of PolyQ, a database of human polyglutamine proteins. (15th March 2016) - Li, Chen; Nagel, Jeremy; Androulakis, Steve; Song, Jiangning; Buckle, Ashley M.
Abstract : Proteins with expanded polyglutamine (polyQ) repeats are involved in human neurodegenerative diseases, via a gain-of-function mechanism of neuronal toxicity involving protein conformational changes that result in the formation and deposition of β-sheet-rich aggregates. Aggregation is dependent on the context and properties of the host protein, such as domain context and location of the repeat tract. In order to explore this relationship in greater detail, here we describe PolyQ 2.0, an updated database that provides a comprehensive knowledgebase for human polyQ proteins. Compared with the previous PolyQ database, our new database provides a variety of substantial updates including detailed biological annotations and search options. Biological annotations in terms of domain context information, protein structural and functional annotation, single point mutations, predicted disordered regions, protein–protein interaction partners, metabolic/signaling pathways, post-translational modification sites and evolutionary information are made available. Several new database functionalities have also been provided, including search using multiple/combinatory keywords, and submission of new data entries. Also, several third-party plug-ins are employed to enhance data visualization in PolyQ 2.0. In PolyQ 2.0 the proteins are reclassified into 3 new categories and contain 9 reviewed disease-associated polyQ proteins, 105 reviewed non-disease polyQ proteins and 146 un-reviewed polyQ proteins (reviewed by UniProt curators). We envisage that this updated database will be a useful resource for functional and structural investigation of human polyQ proteins. Database URL: http://lightning.med.monash.edu/polyq2/